Impact and adoption of drought tolerant maize varieties and interrelated agricultural technologies on rural households productivity and welfare - Oyetunde-Usman, Z. (University of Greenwich, 2021)
Over the years, climatic variations have persistently induced technological interventions in developing countries and were strategic in varietal development and modification of agronomical practices in developing countries. In addition, there are overwhelming records of impact on productivity and welfare of rural farm households. Despite these efforts, low adoption continues to be a huge problem and a clog to meeting sustainable agricultural development goals. This research contributes to the large debate on adoption determinants and impacts with a specific focus on Drought Tolerant Maize technology by the better understanding interrelation of DTMVs with other agricultural technology adopted by maize farm households, the adoption intensity, the joint adoption impact with complementary smart agricultural practices and how farmers perceived DTMVs attributes influences their adoption decisions. Chapter 1 provides a general introduction to an overview of various modifications in agricultural technology in developing countries. It introduces agricultural technology in the study area, the broad objectives, research questions, and methodology of the study. The remaining chapters are individual publications that form the core part of this thesis. Chapter 2 expands on the historical evolution of agricultural technology in developing countries, with a focus on how sub-Saharan Africa differs in the slow adoption and spread of agricultural technology. It further highlights how key socioeconomic characteristics of farm households influence the adoption of agricultural technology with examples of past studies and their results. The chapter concludes that there is so much to be gained from enhancing the understanding of the heterogeneity that exists in key popular indicators in adoption studies. Chapter 3 examines the simultaneous adoption of DTMVs and other CSAPs. It explores the existing complementarity and substitutability relationship and adoption intensity of identified agricultural technology. This chapter helps to highlight that it is important to examine the role of other technologies in the adoption of a specific technology. It importantly shows the varying degree of relationships of DTMVs with other CSAPs, most especially with manure. In addition, this chapter shows that it is not enough to introduce innovation without understanding the existing constraints to adoption and the limit to the number of agricultural technology farm households can adopt simultaneously adopt. Chapter 4 leveraged the complementarity status of DTMVs and manure to estimate their joint adoption impact on productivity and welfare. the findings highlight the higher gains on productivity, per-capita total expenditure, and per-capita food expenditure when DTMVs and manure are jointly adopted compared to individual cases. The findings also reiterate the role of institutional factors such as access to extension and loans in combinatory and individual driving adoption of DTMVs and manure. The results recommend the need to incorporate manure in policy and programmes targeted at enhancing the adoption of DTMVs. Chapter 5 experimentally elicits information on maize farm households’ preference heterogeneity for DTMVs attribute. The findings show the need to highlights that there is existing preference heterogeneity in farm households’ choice of DTMVs attributes that influence their adoption decision. Promoting the adoption of DTMVs should consider leveraging on attributes of DTMVs that are high yielding, high drought tolerant, high resistant to Striga, and high nitrogen use of efficiency, and this should be the centre of promotion programmes on DTMVs. The study further recommends the need to use platforms such as farmers' groups and enhance extension access on learning and promotions of preferred attributes of DTMVs.